Ayi Kwei Armah’s Intellectuals of the African Renaissance - Mami,Fouad (2011)
Ayi Kwei Armah is a living Ghanaian novelist and cultural activist. His life and body of novelistic experiments show a meticulous preoccupation with Africa’s present cultural crisis. His seven novels to date, in addition to his autobiography entitled The Eloquence of the Scribes (2006), all illustrate a relentless intellectual campaign for articulating the ways in which the ”right” and committed intellectuals can be singled out from what he takes as multitudes of pseudo- or parvenu academics. For Armah, a carefully devised and administered educational system should form the basis for a reformed African ethos. This article explores Armah’s call for renovating the present educational philosophy that aims to promote a new idea of Africa. Constructing an authentic educational system is justified by him through the need to supersede the devastating effects imposed by and instituted through colonial education. Below is an attempt to debate Armah’s deconstructive approach of the colonial educational pattern. Similarly, viable prospects of a change of perspective are reviewed. In founding schools throughout Africa and granting scholarships in metropolitan universities to African students, Armah thinks, colonial powers only meant to maintain control, even after the end of their direct occupation.